Vegetarian diets in the nutrition of pregnant women (Research, Society and Development, 2022)
Vegetarian diets have increased around the world in recent decades, and these are consistently associated with better health outcomes, however, it remains unclear whether a vegetarian diet is appropriate for pregnancy. Maternal diet is not only correlated with the health of the fetus’s health but seems relevant for that of the mother as well. This review aims to present an overview of the potential effects of vegetarianism during pregnancy. The study was carried out by literature review. Scientific articles, books and licensed websites published in the last 10 years, in Portuguese and English, were used. Although vegetarian diets can cause nutritional deficiencies such as protein, iron, calcium, omega 3, and vitamin B12, the substantial evidence suggests that well-planned vegetarian diets can be considered safe during pregnancy. However, they require a strong awareness of a balanced intake of essential nutrients, necessitating a pre-gestational and gestational nutritional assistance to avoid problems with maternal nutrition and the resulting iatrogenic effects.